1999
DOI: 10.1076/clin.13.3.283.1743
|View full text |Cite
|
Sign up to set email alerts
|

Practice Effects on Commonly Used Measures of Executive Function Across Twelve Months

Abstract: Fifty men (age M = 32.50; education M = 14.98 years) were administered the Wisconsin Card Sorting Test (WCST), Ruff Figural Fluency Test (FFT), Verbal Concept Attainment Test (VCAT) Trail Making Test, Parts A and B (TMT), and F-A-S Verbal Fluency at baseline and 12 months later. WCST, FFT, and VCAT scores improved significantly over a 12-month interval. In contrast, TMT and F-A-S scores did not change. Level of intellectual ability failed to moderate the effect of previous testing upon performance. Suggestions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
115
4
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(127 citation statements)
references
References 12 publications
6
115
4
2
Order By: Relevance
“…Prior studies have shown that figural memory tests, which measure a similar cognitive domain as the CVMT, demonstrate a significant practice effect on short-term readministration, while practice effects have generally not been reported for Trail's B. 36,37 Nevertheless, practice effects based upon procedural learning, (i.e., improved performance due to increasing familiarity with the test rules), cannot be excluded, particularly in this cohort of generally well-educated patients with high levels of occupational functioning. 38,39 Future longitudinal studies of cognitive function in chronic hepatitis C patients should incorporate tests with multiple alternate forms as well as a control group of patients not receiving antiviral therapy to minimize any potential procedural learning or practice effects.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that figural memory tests, which measure a similar cognitive domain as the CVMT, demonstrate a significant practice effect on short-term readministration, while practice effects have generally not been reported for Trail's B. 36,37 Nevertheless, practice effects based upon procedural learning, (i.e., improved performance due to increasing familiarity with the test rules), cannot be excluded, particularly in this cohort of generally well-educated patients with high levels of occupational functioning. 38,39 Future longitudinal studies of cognitive function in chronic hepatitis C patients should incorporate tests with multiple alternate forms as well as a control group of patients not receiving antiviral therapy to minimize any potential procedural learning or practice effects.…”
Section: Discussionmentioning
confidence: 99%
“…10,14,27 Longitudinal studies have typically used the verbal and semantic fluency task, which is not subject to practice effects. 54,55 Consequently, improvement in language function over time cannot be attributed solely to repeated test presentation. Mavaddat and colleagues 18 followed 47 patients with a favorable neurological outcome (ie, GOS scores of 4 or 5 corresponding to "moderate disability" and "good recovery," respectively) between 6 and 24 months after aSAH.…”
Section: Languagementioning
confidence: 99%
“…Although inhibition improved within 1 year after aSAH, cognitive flexibility and attention showed no improvement over the same time period. Results from longitudinal studies, however, must be interpreted with caution, because tests of executive function may be subject to practice effects (eg, Stroop test, 54 Trail Making Test, 54 Wisconsin Card Sorting Test 55 ). Studies that found improvement in response inhibition and cognitive flexibility over time 27,28 used the Stroop test and Trail Making Test, both of which may have practice effects.…”
Section: Executive Functionmentioning
confidence: 99%
“…Thus, "improvements" in function may represent practice effects from repeated test administration, particularly on tests such as the Wisconsin Card Sorting Test (see Chou et al, 2007) in which practice effects can be large even across a 1-year interval in testing (Basso et al, 1999). Furthermore, controlled studies of cognition during abstinence may help to clarify conflicting findings from a cross-sectional study, in which MA-using participants who were abstinent for 3 months had worse verbal memory performance than MA-using participants who were continuously using or had relapsed during treatment (Simon et al, 2004).…”
mentioning
confidence: 99%